HUBUNGAN PARITAS DENGAN KEJADIAN PARTUS PREMATURUS IMMINENS PADA IBU HAMIL - Mariana, Frani; Istiqamah; Nida Herni (LPPM Universitas Sari Mulia, 2023)
Background: Preterm birth, according to WHO criteria, is defined as birth occurring between 22 and 37 weeks of gestation with a fetal weight of 500 grams. Preterm birth is one of the leading causes of perinatal morbidity and mortality worldwide, contributes to the development of neonatal pathologies, and significantly impacts medical, demographic, economic, and social conditions (Arstanalievna et al., 2022). Parity is one of the predisposing factors for preterm birth, as it can affect the mother's health status during pregnancy. The incidence of preterm birth is higher among primiparous women, around 9.5%, compared to 7.5% in multiparous women (Herman and Joewono, 2020). Objective: To analyze the relationship between parity and the incidence of Partus Prematurus Imminens (PPI) in pregnant women. Method: This research used a quantitative analytical method with a cross-sectional approach. The sampling technique was total sampling, involving 93 pregnant women. Bivariate analysis was conducted using the chi-square test. Results: Among the 93 pregnant women who experienced Partus Prematurus Imminens (PPI), the highest parity was found in nulliparous women, totaling 37 individuals (39.8%). The chi-square statistical test showed a p-value = 0.011 < α = 0.05 with a confidence level of 95%. Conclusion: There is a significant relationship between parity and the incidence of Partus Prematurus Imminens (PPI). For the community, particularly pregnant women with risk factors, it is important to recognize the causes of preterm labor to take early preventive measures. Health workers are expected to provide optimal services to the community, especially in prenatal care. Keywords: Partus Prematurus Imminens, Parity, Pregnant Women